A method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor
By forming an Ag/TiO2 composite oxide film on the surface of the anode foil of the aluminum electrolytic capacitor, the problem of low dielectric constant of the anode foil is solved, the specific capacitance is improved, and the demand for high-performance capacitors is met.
Patent Information
- Application Number
- CN202411961386.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-23
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The dielectric constant of the existing aluminum electrolytic capacitor anode foil is low, resulting in insufficient specific capacitance and cannot meet the needs of high-performance capacitors.
By forming a composite oxide film with a high dielectric constant on the surface of the anode foil, the specific method is to coat the Ag/TiO2 precursor liquid on the corrosion foil and perform anodizing treatment at a high temperature to transform the crystal structure of TiO2, thereby increasing the dielectric constant of the oxide film.
The Ag doping leads to the transformation of the TiO2 crystal structure into a rutile phase, which significantly increases the dielectric constant of the composite oxide film, thereby increasing the specific capacitance of the anode foil and meeting the needs of high-performance capacitors.
Smart Images

Figure CN119764063A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum electrolytic capacitor anode foil, and in particular to a method for manufacturing anode foil of an aluminum electrolytic capacitor with a high dielectric constant and ultra-high voltage. Background Art
[0002] After electrochemical corrosion, the aluminum foil is placed in a chemical solution with oxidation ability for anodization, which can form a barrier type anodized film (also called barrier layer, dense film layer, etc.) on the foil surface. In the aluminum electrolytic capacitor, this anodized film can be used as the actual working anode, and its physical and chemical properties also affect the performance of the aluminum electrolytic capacitor in terms of capacitance, leakage current, loss and service life. According to the calculation formula of the capacitance of the aluminum electrolytic capacitor C = (ε0ε r )S / d, where d represents the distance between the two plates, S represents the specific surface area of the anode foil, and ε r It represents the relative dielectric constant of the dielectric. From the capacitance formula, it can be seen that there are three main ways to increase the specific capacitance C: 1) increase the specific surface area S; 2) reduce the thickness d of the anodized film; 3) increase the relative dielectric constant ε of the dielectric film r For ultra-high voltage anode foil, since the specific surface area of the corroded foil cannot be infinitely increased, the dielectric constant ε of the oxide film is increased. r It is an effective way to increase specific capacitance.
[0003] Current research shows that compounding high dielectric constant valve metal oxides into traditional anode Al2O3 films to form composite anodic oxide films can increase the relative dielectric constant of the dielectric layer, thereby increasing the specific capacitance of the anode foil. Valve metal oxide TiO2 has a large relative dielectric constant (ε r =48~118), low dielectric loss and low crystal transformation temperature (550℃~800℃), and is considered to be a promising material. When preparing composite anodized films, the annealing temperature should not exceed 600℃. Because when the temperature exceeds this, high-purity aluminum is easy to melt and recrystallize, resulting in pore collapse, specific surface area shrinkage and specific capacitance reduction. At this temperature, the main crystal phase of TiO2 is the anatase phase with a low relative dielectric constant (ε r =48, the annealing temperature is above 300°C), which is still limited in improving the relative dielectric constant of the oxide film. Summary of the invention
[0004] Purpose of the invention: In view of the above problems, the present invention provides a method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor.
[0005] The technical solution adopted by the present invention is a method for manufacturing anode foil of a high dielectric constant ultra-high voltage aluminum electrolytic capacitor, comprising the following steps:
[0006] (1) Preparation of ultra-high voltage corrosion foil: the cut aluminum foil is pre-treated in the order of before alkaline solution and after acid solution, and then three-stage direct current electrochemical corrosion is carried out in a mixed acid solution of hydrochloric acid and sulfuric acid to obtain the desired ultra-high voltage corrosion foil;
[0007] (2) Preparation of Ag / TiO2 precursor solution: Tetrabutyl titanate and solvent are uniformly mixed at a volume ratio of 1:1-1:5, water is added to the above solution at a volume ratio of 1:5-1:10 to tetrabutyl titanate, and then a chelating agent is added, and then a stabilizer is added to adjust the pH value to 4.5-5.5, and the mixture is uniformly mixed for about 60 minutes to 90 minutes to obtain a yellow transparent solution. Then, different proportions of Ag-containing + The compound is stirred for 1h-3h to obtain a Ag / TiO2 precursor solution. + The compound includes one or more of AgNO3, AgNO2, AgCl or AgI.
[0008] (3) Dip coating treatment, vertically immersing the corrosion foil prepared in step (1) into the Ag / TiO2 precursor solution prepared in step (2), and pulling it out at a uniform and stable speed, and drying it at 70°C-120°C for 15min-30min after taking it out; the immersion-pulling times are 1 time to 10 times.
[0009] (4) Preparation of ultra-high voltage anode foil: The corroded foil treated in step (3) is subjected to anodizing treatment at a voltage of 550V-1000V, a forming temperature of 70°C-90°C, and a treatment time of 10min-20min. The formed foil is then annealed at 500°C-600°C for 10min-30min, and then taken out and cleaned to remove surface ash.
[0010] Preferably, in step (2), the solvent is ethanol.
[0011] Preferably, in the step (2), before adding water, a chelating agent is added in a volume ratio of 1:1 to 1:5 to tetrabutyl titanate, and mixed evenly; the chelating agent includes one or more of ethyl acetate, propyl acetate, acetone, acetylacetone or isobutyl acetate, preferably ethyl acetate. The stabilizer is nitric acid.
[0012] Preferably, in step (2), the Ag content in the Ag / TiO2 precursor solution is 0 mol%-15 mol%, preferably 1 mol%-7 mol%.
[0013] Preferably, in step (4), when the ultrahigh voltage corrosion foil is formed, the forming electrolyte is a compound with a mass fraction of 5-25%, and the compound includes one or more of boric acid, ammonium pentaborate, phosphoric acid or ammonium adipate, preferably ammonium pentaborate.
[0014] Beneficial effects of the present invention: Since the doping temperature of Ag is relatively low (about 400°C), along with the introduction of Ag, the crystal structure of TiO2 tends to transform from anatase phase to rutile phase, which will greatly increase the dielectric constant of TiO2, thereby indirectly improving the dielectric constant of the composite anodized film, and can further increase the specific capacitance of the anode foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Schematic diagram of the high dielectric constant composite film structure of the present invention.
[0016] Figure 2 This is a SEM image of the surface of the ultra-high voltage anode foil prepared in Example 1.
[0017] Figure 3 This is a SEM image of the cross section of the ultra-high voltage anode foil prepared in Example 1.
[0018] Figure 4 This is a SEM image of the surface of the ultra-high voltage anode foil prepared in Example 2.
[0019] Figure 5 This is a SEM image of the cross section of the ultra-high voltage anode foil prepared in Example 2.
[0020] Figure 6 This is a SEM image of the surface of the ultra-high voltage anode foil prepared in Example 3.
[0021] Figure 7 This is a SEM image of the cross section of the ultra-high voltage anode foil prepared in Example 3.
[0022] Figure 8 This is the element distribution on the surface of the ultra-high voltage anode foil prepared in Example 3.
[0023] Fig. 9 Schematic diagram, SEM image, and element distribution of the ultra-high voltage anode foil composite dielectric film layer prepared in Example 3.
[0024] Fig.10 This is the XRD pattern of the surface of the ultra-high voltage anode foil prepared in Example 3.
[0025] Fig.11 The anode voltage boost curves of the ultrahigh voltage anode foils prepared in Examples 1, 2, and 3.
[0026] Fig.12 The open circuit potential-time curves of the ultrahigh voltage anode foils prepared in Examples 1, 2 and 3.
[0027] Fig.13 Cyclic voltammetry curves of the ultra-high voltage anode foils prepared in Examples 1, 2, and 3.
[0028] Fig.14 Tafel polarization curves of the ultrahigh voltage anode foils prepared in Examples 1, 2, and 3.
[0029] Fig.15 The AC impedance curves of the ultra-high voltage anode foils prepared in Examples 1, 2, and 3. DETAILED DESCRIPTION
[0030] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is described in detail below in conjunction with specific implementation methods and drawings.
[0031] The present invention provides a method for manufacturing an ultra-high voltage aluminum electrolytic capacitor anode foil with a high dielectric constant composite film, wherein the high dielectric constant composite film is an Al2O3-Ag / TiO2 composite anode oxide layer. Studies have shown that doping metal in TiO2 can enable the material to obtain a larger dielectric constant while having lower dielectric loss and frequency stability. In the present invention, when preparing an ultra-high voltage anode foil with a high dielectric constant composite oxide film, Ag doping (such as Figure 1 ), and then the Al2O3-Ag / TiO2 composite anodic oxide film was prepared on the surface of the aluminum foil by the sol-gel method, and the crystal phase was obtained by annealing at 550℃. Under the induction of Ag doping, the TiO2 crystals transformed from the anatase phase to the rutile phase. During the phase transition, the TiO2 grain size increased, and the TiO6 octahedron was distorted, which weakened the interaction between the lattices, reduced the polarization resistance, and increased the dielectric constant of the composite anodic oxide film, thereby further increasing the specific capacitance of the ultra-high voltage anode foil.
[0032] Example 1
[0033] (1) Preparation of ultra-high voltage corrosion foil: the cut aluminum foil is pre-treated in the order of before alkaline solution and after acid solution, and then three-stage direct current electrochemical corrosion is carried out in a mixed acid solution of hydrochloric acid and sulfuric acid to obtain the desired ultra-high voltage corrosion foil;
[0034] (2) Preparation of ultra-high voltage anode foil: The corroded foil treated in step (1) is subjected to anodizing treatment at a voltage of 600 V, a forming temperature of 80° C., and a treatment time of 10 min. The formed foil is then annealed at 510° C. for 20 min, and then taken out and cleaned to remove surface ash. In this embodiment, the forming electrolyte is ammonium pentaborate with a mass fraction of 10%.
[0035] Figure 2 This is a SEM image of the surface of the ultra-high voltage anode foil prepared in this embodiment. The etched holes are consistent with the "circular" macropores of the ultra-high voltage anode foil.
[0036] Figure 3This is a SEM image of the cross section of the ultra-high voltage anode foil prepared in this embodiment. The etched holes are consistent with the "cylindrical" etched holes of the ultra-high voltage anode foil.
[0037] Embodiment 2:
[0038] (1) Same as step (1) of Example 1.
[0039] (2) Preparation of TiO2 precursor solution: Tetrabutyl titanate and solvent are uniformly mixed in a volume ratio of 1:2.5, and then a chelating agent is added in a volume ratio of 1:2 to tetrabutyl titanate and stirred evenly, and then water is added in a volume ratio of 1:5 to tetrabutyl titanate to the above solution, and uniformly mixed for about 60 min-90 min to obtain a yellow transparent solution. In this embodiment, the solvent is ethanol and the chelating agent is ethyl acetate.
[0040] Tetrabutyl titanate is very easy to hydrolyze. Ethyl acetate is added to the solution in step (2) as a chelating agent to control the hydrolysis rate of tetrabutyl titanate. By adding a certain amount of inorganic acid to the sol system, hydrolysis can be inhibited, the colloidal ions are positively charged, and the micelles are prevented from agglomerating. Adding an appropriate amount of water to the sol-gel system can promote the hydrolysis of tetrabutyl titanate to form a continuous and uniform film. However, too much water can greatly shorten the gel time of the TiO2 sol, which will reduce the surface area and pore volume of the TiO2 film, and sometimes it will quickly hydrolyze to form a precipitate. If the water content in the sol is too low, a discontinuous film will be formed.
[0041] (3) Dip coating treatment: vertically immerse the corrosion foil prepared in step (1) into the Ag / TiO2 precursor solution prepared in step (2), and pull it out at a uniform and stable speed, and then dry it at 70°C-120°C for 30 minutes. The number of immersion-pulling times in this embodiment is 2 times.
[0042] (4) Same as step (2) in Example 1.
[0043] Figure 4 This is a SEM image of the surface of the ultra-high voltage anode foil prepared in this embodiment. The etched holes conform to the "circular" large holes of the ultra-high voltage anode foil, and the hole mouths are sharpened and appear "fluid-like". This embodiment successfully prepares a composite oxide layer on the surface of the chemically formed foil.
[0044] Figure 5 This is a SEM image of the cross section of the ultra-high voltage anode foil prepared in this embodiment. The etched holes are consistent with the "cylindrical" etched holes of the ultra-high voltage anode foil.
[0045] Embodiment 3:
[0046] (1) Same as step (1) of Example 1.
[0047] (2) Preparation of Ag / TiO2 precursor solution: Tetrabutyl titanate and solvent are uniformly mixed in a volume ratio of 1:2.5, and then a chelating agent is added in a volume ratio of 1:2 to tetrabutyl titanate and stirred evenly. Then, water is added in a volume ratio of 1:5 to tetrabutyl titanate to the above solution, and mixed evenly for about 60 minutes to 90 minutes to obtain a yellow transparent solution. In this embodiment, the solvent is ethanol and the chelating agent is ethyl acetate. Finally, different proportions of AgNO3 are added to the above yellow solution and stirred evenly for 1 hour to 3 hours to obtain an Ag / TiO2 precursor solution. In this embodiment, after the AgNO3 solution is added, Ag + The content is 5 mol%.
[0048] Tetrabutyl titanate is very easy to hydrolyze. Ethyl acetate is added to the solution in step (2) as a chelating agent to control the hydrolysis rate of tetrabutyl titanate. By adding a certain amount of inorganic acid to the sol system, hydrolysis can be inhibited, the colloidal ions are positively charged, and the micelles are prevented from agglomerating, which plays a role in extending the hydrolysis time and ensuring that AgNO3 is completely dissolved. Adding an appropriate amount of water to the sol-gel system can promote the hydrolysis of tetrabutyl titanate to form a continuous and uniform film. However, too much water can greatly shorten the gel time of the TiO2 sol, which can reduce the surface area and pore volume of the TiO2 film, and sometimes it can quickly hydrolyze to form a precipitate. If the water content in the sol is too low, a discontinuous film will be formed, and AgNO3 cannot be completely dissolved.
[0049] (3) Same as step (3) in Example 2.
[0050] (4) Same as step (2) in Example 1.
[0051] Figure 6 The SEM image of the etched holes on the surface of the ultra-high voltage anode foil prepared for this embodiment is consistent with the "circular" large holes of the ultra-high voltage anode foil, and the hole mouths are sharpened and appear "fluid-like". This embodiment successfully prepares a composite oxide layer on the surface of the chemically formed foil.
[0052] Figure 7 This is a SEM image of the cross section of the ultra-high voltage anode foil prepared in this embodiment. The etched holes are consistent with the "cylindrical" etched holes of the ultra-high voltage anode foil.
[0053] Figure 8 This is the element distribution on the surface of the ultra-high voltage anode foil prepared in this embodiment. The Ti and Ag elements on the surface of the embodiment are obviously and evenly distributed on the foil surface.
[0054] Fig. 9 The schematic diagram, SEM image, and element distribution of the composite dielectric film layer of the ultra-high voltage anode foil prepared in this embodiment show that the Al-Ti composite oxide film layer structure can be clearly observed.
[0055] Fig.10This is the XRD pattern of the surface of the ultra-high voltage anode foil prepared in this embodiment. After Ag doping, the composite TiO2 on the surface of the embodiment undergoes a transformation from a perovskite phase to a rutile phase.
[0056] Electrochemical analysis was performed on the processes of Examples 1, 2, and 3, and the specific steps are as follows:
[0057] The measurements and polarization curve (Tafel) measurements, open circuit potential-time curves, cyclic voltammetry curves and electrochemical impedance spectroscopy (EIS) were carried out in a CHI660E electrochemical station. The reference electrode and counter electrode were saturated calomel electrode (SCE) and platinum electrode, respectively, with an exposure area of 1 cm 2 The anode foil is the working electrode, and all tests are performed at room temperature. Before the test, the open circuit potential test (OCP) is performed for 15 minutes to reach a stable state, and then EIS measurements are performed at an open circuit potential voltage with a 10mV interference signal in the frequency range of 100kHz-10mHz. The EIS data are fitted and analyzed using ZSimpWin software.
[0058] Fig.11 The anode voltage boost curves of the ultra-high voltage anode foils prepared in Examples 1, 2, and 3 show that the starting voltages of the anode foils impregnated with different TiO2 are all lower than those of the uncoated anode foil, and the starting voltage of Example 3 is between that of Sample Examples 1 and 2, indicating that Ag doping causes the TiO2 in the sample to be in the rutile phase, and its unit lattice is smaller and more compact, which can make a certain contribution to the voltage resistance of the anode foil surface.
[0059] Fig.12 The open circuit potential-time curves of the ultrahigh voltage anode foils prepared in Examples 1, 2 and 3 show that the test curves of all examples tend to be horizontal straight lines, indicating that the electrode surface and the test environment are in a relatively stable state. The open circuit potential of Example 1 is greater than that of Examples 1 and 2, indicating that after the composite oxide film is formed on the surface of the anode foil, the open circuit potential of the examples decreases.
[0060] Fig.13 The cyclic voltammetry curves of the ultra-high voltage anode foils prepared in Examples 1, 2, and 3 are shown. The change in the total area of the curves represents the change trend of the specific capacitance of the samples. The curve area of Example 3 is the largest, indicating that its specific capacitance is the largest. Secondly, as the number of cycles increases, the shape of the curve remains basically unchanged, indicating that the embodiments of the present invention have stable cycle performance.
[0061] Fig.14 The Tafel polarization curves of the ultra-high voltage anode foils prepared in Examples 1, 2, and 3 show that the corrosion potential shifts positively and the corrosion current density shifts negatively from Example 1 to 3, indicating that the corrosion resistance of the formed foil is gradually enhanced, but the corrosion rate is gradually reduced. This may be attributed to the increase in the types of barrier oxide layers on the sample surface and the increase in thickness.
[0062] Fig.15 The AC impedance curves of the ultra-high voltage anode foils prepared in Examples 1, 2, and 3 show that in the Nyquist plots of the embodiments of the present invention, the spectra all deviate from the semicircular arc trajectory and appear as a circular arc, which is considered to be a typical capacitive reactance arc with capacitive properties. The impedance modulus |Z| of the low-frequency region sample gradually decreases with the introduction of the composite dielectric layer and the Ag doping thereof, indicating that the composite dielectric layer generated on the surface of the anode foil is conducive to reducing the capacitive reactance and promoting the transfer of electrons.
[0063] The ultrahigh voltage corrosion foils prepared in Examples 1, 2 and 3 were formed at 600 V, and then the specific capacitance and leakage current data of the formed foils were tested using an LCR digital bridge. The test frequency was 100 Hz, and the electrolyte was a 10 wt % ammonium pentaborate solution.
[0064] Table 1 shows the relevant parameters of the etched foil in the embodiment of the present invention. As can be seen from Table 1, the specific capacitance increases from embodiment 1 to embodiment 3, and the loss factor increases first and then decreases. This indicates that a composite oxide film with a high dielectric constant is formed on the surface of the ultra-high voltage anode foil, which increases its specific capacitance. At the same time, after heat treatment, micropores and interface defects exist at the interface of the composite oxide film, so that the tanδ of the formed foil increases first and then decreases.
[0065] Table 1
[0066]
[0067] It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor, characterized in that: The following steps are involved: (1) Preparation of ultra-high voltage corrosion foil: the cut aluminum foil is pre-treated in the order of before alkaline solution and after acid solution, and then three-stage direct current electrochemical corrosion is carried out in a mixed acid solution of hydrochloric acid and sulfuric acid to obtain the desired ultra-high voltage corrosion foil; (2) Preparation of Ag / TiO2 precursor solution: Tetrabutyl titanate and solvent are uniformly mixed in a volume ratio of 1:1-1:5, water is added to the above solution in a volume ratio of 1:5-1:10 to tetrabutyl titanate, and then a chelating agent is added, and then a stabilizer is added to adjust the pH value to 4.5-5.5, and the mixture is uniformly mixed for about 60 min-90 min to obtain a yellow transparent solution; then different proportions of Ag-containing + The compound is stirred for 1h-3h to obtain a Ag / TiO2 precursor solution; the Ag-containing + The compound includes one or more of AgNO3, AgNO2, AgCl or AgI. (3) immersion coating treatment, vertically immersing the corrosion foil prepared in step (1) into the Ag / TiO2 precursor solution prepared in step (2), uniformly and steadily pulling it out, and drying it at 70°C-120°C for 15min-30min after taking it out; the immersion-pulling times are 1 time-10 times; (4) Preparation of ultra-high voltage anode foil: the etched foil after treatment in step (3) is subjected to anodizing treatment at a voltage of 550V-1000V, a forming temperature of 70°C-90°C, and a treatment time of 10min-20min; then the formed foil is annealed at 500°C-600°C for 10min-30min, taken out, cleaned, and the surface ash is removed.
2. The method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor according to claim 1, characterized in that: In the step (2), the solvent is ethanol.
3. The method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor according to claim 2, characterized in that: In the step (2), before adding water, a chelating agent is added in a volume ratio of 1:1 to 1:5 to tetrabutyl titanate and mixed evenly.
4. The method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor according to claim 3, characterized in that: The chelating agent includes one or more of ethyl acetate, propyl acetate, acetone, acetylacetone or isobutyl acetate.
5. The method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor according to claim 4, characterized in that: The chelating agent is ethyl acetate, and the stabilizer is nitric acid.
6. The method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor according to claim 5, characterized in that: In the step (2), the Ag content in the Ag / TiO2 precursor solution is 0 mol%-15 mol%.
7. The method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor according to claim 6, characterized in that: The Ag content in the Ag / TiO2 precursor solution is 1 mol%-7 mol%.
8. The method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor according to claim 7, characterized in that: In the step (4), when the ultra-high voltage corrosion foil is formed, the forming electrolyte is a compound with a mass fraction of 5-25%, and the compound includes one or more of boric acid, ammonium pentaborate, phosphoric acid or ammonium adipate.
9. The method for manufacturing anode foil of high dielectric constant ultra-high voltage aluminum electrolytic capacitor according to claim 8, characterized in that: The compound is ammonium pentaborate.
Citation Information
Cited By
Composite anode foil based on aluminum substrate and preparation method thereof
CN122224693A
Aluminum-based composite anode foil and its preparation method
CN122224693B